2016
DOI: 10.1111/idj.12244
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of undergraduate dental students in Japan: English competency and willingness to study abroad

Abstract: Japanese educational authorities and dental schools may need to consider a range of incentives and motivational strategies to nurture clinicians, educators and researchers who can function confidently in an increasingly borderless world. These could include increasing exposure to English language skills through mandatory lectures and seminars in English, increasing the range of inbound international students through student exchange programmes and encouraging students to develop and communicate with internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 5 publications
0
20
0
2
Order By: Relevance
“…Thus, it may be important to focus on why the more less‐open dental students did not go to study abroad in order to better encourage them to do so. Considering about the concerns of less‐open students in this study, providing experience with English and “international friends” could be one method for helping students develop their confidence, as has been reported in the past (Takehara et al, ). Additionally, the less‐open students were concerned with costs and specialized knowledge required to study abroad to the same level as open students.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, it may be important to focus on why the more less‐open dental students did not go to study abroad in order to better encourage them to do so. Considering about the concerns of less‐open students in this study, providing experience with English and “international friends” could be one method for helping students develop their confidence, as has been reported in the past (Takehara et al, ). Additionally, the less‐open students were concerned with costs and specialized knowledge required to study abroad to the same level as open students.…”
Section: Discussionmentioning
confidence: 90%
“…Os dados encontrados quanto à proficiência em idiomas revelam dificuldade dos estudantes para comunicação em línguas estrangeiras, o que pode representar potencial barreira frente ao processo de atualização científica ou internacionalização da Odontologia [21][22][23] . Embora não seja a língua oficial da maioria dos países europeus e latino-americanos, a língua inglesa é comum ao intercâmbio científico e cultural, sendo, portanto, importante como segundo idioma.…”
Section: Discussionunclassified
“…Na Arábia Saudita, pesquisadores constataram a necessidade de maior foco ao ensino da língua inglesa na educação préuniversitária de estudantes de Odontologia a fim de melhor prepará-los aos desafios da educação universitária 24 . Da mesma forma, com o objetivo de aprofundar o conhecimento das motivações de estudantes japoneses e fornecer informações a respeito da internacionalização da Odontologia, estudos concluíram que são necessários incentivos e estratégias motivacionais para formar clínicos, educadores e pesquisadores atuantes em um mundo sem fronteiras 22,23 .…”
Section: Discussionunclassified
“…5 Study showed that in non-English speaking country such as Japan, the competency and con dence in the English language could be one of the biggest obstacles for dental students to study abroad. 6 Poor English ability may limit the possibility of career path for the dental students. Therefore, a better dental English education mode should be discussed to meet the demand of English application in Chinese dental students.…”
Section: Future Expectation Of Dental English Education In Chinamentioning
confidence: 99%